Microbial Treatment of Domestic Wastewater Treatment Plant Sludge by Liquid State Bioconversion Process - Alam, Md. Zahangir (2002)
The study of microbial treatment of domestic wastewater treatment plant (DWTP) sludge by liquid state bioconversion (LSB) process was conducted by several approaches. A total of 70 strains of filamentous fungi were isolated from three different sources (wastewater, DWTP sludge and landfill leachate), which belonged to the genera of Penicillium (39 strains), Aspergillus (14 strains), Trichoderma (12 strains), Spicaria (3 strains) and Hyalojlorae (2 strains). In the screening test, the fungal strains WWZPI003 (Penicillium corylophilum), SCahmAI03 (Aspergillus niger), SCahmTI05 (Trichoderma hamianum) and PC-9 (Phanerochaete chrysosporium), among their respective groups of Penicillium, Aspergillus, Trichoderma and Basidiomycete, played potential roles in tenns of separation, biodegradation and filtration of treated DWTP sludge. The results of the compatible mixed culture optimization study showed a compatible growth of the mixed culture for PIA, PIPC and AfPC and the combinations PIT, AfT and T/PC were observed to be incompatible cultures for the bioconversion of the sludge. Among the combinations, the potential compatible mixed culture of PIA was selected for DWTP sludge treatment in LSB process. The results obtained in optimum LSB processes indicated that wheat flour (WF) at a concentration of 1.5- 2% (w/w) was a better co-substrate in sludge containing medium, with optimum initial pH of 4.5-5.5, temperature of 33-350C and inoculum size of 2-3% (v/w). Bioconversion of DWTP sludge was highly influenced by agitation and aeration rate that were 150-200 rpm and 0.5 vvrn, respectively. In a settleability and dewaterability study, 86.45% of TSS was settled in treated sludge while 4.35% in untreated sample after one minute of settling operation. The results for specific resistance to filtration (SRF) showed that the fungal inoculum had significant potentiality to reduce SRF by 99.8% and 98.7% for 1% and 4% of sludge, respectively. Bioconversion efficiency was higher by 0.2-20% in fermenter than in the shake flask in terms of biosolids accumulation and biodegradation of organic matters in sludge. In developed bioconversion processes, 93.75 g/kg of biosolids was enriched with fungal biomass protein and nutrients (NPK), and 98.84% of TSS, 98.22% of TDS, 97.33% of turbidity, 80.24% of soluble protein, 98.81% of reducing sugar and 92.66% of COD in treated sludge supernatant were removed after 8 days of treatment. SRF (1.39xlO12 m/kg) was decreased tremendously by the microbial treatment ofDWTP sludge after 6 days of fermentation. LSB process for microbial treatment of DWTP sludge is a new biotechnological approach that has economic value and is non-hazardous as well as environmental friendly, and therefore may be encouraging to sludge management strategy in future applications.